The Effect of Converting to Internal Financial Reporting Standards on The Financial Performance of Saudi Joint-Stock Companies - Abdulrahman, Najla Ibrahim; Algarni, Elaf Naser (Journal of Economic, Administrative and Legal Sciences, 2021)
The aim of the research is to study the effect of converting to internal financial reporting standards on the financial performance of Saudi joint-stock companies. Thought testing the following hypothesis: there is an effect of converting to internal financial reporting standards on gross profit, net income, total asset and total equity. The sample contained six joint-stock companies from basic materials sector. Using the financial statements for five years from 2014 to 2018. The study findings show that there is positive effect of converting to internal financial reporting standards on gross profit and total equity. Also, there is an effect of converting to internal financial reporting standards on net income and total assets. Therefore, converting to internal financial reporting standards effect the financial performance of Saudi joint-stock. The important recommendations are report the effect of converting to internal financial reporting standards on all elements in the financial statements of Saudi joint-stock companies in the clarifications.